Features of innovative development of a mineral-raw complex in modern conditions - I. G. Polyanskaya; E. A. Atamanova (Экономика региона, 2010)
The article discusses the necessity and topicality of innovative development of mineral-raw complex branches having taken into account the thesis «about transition from raw to innovative economy». Tendencies, contradictions and perspectives of working out and introducing of technical and technological, institutional and marketing innovations at various stages of bowels using are marked on the basis of the analysis of the level of innovative introductions, both in branches, and in separate vertically-integrated structures. Special attention is given to the leading role of the state in the formation of conditions for attraction of private investments (both domestic and foreign) in the process of innovative development of the complex.